Identification of Cancer lactatus Linnaeus, 1758 with Lophozozymus pictor (Fabricius, 1798) and reversal of precedence (Crustacea: Decapoda: Brachyura: Xanthidae) - Low, Martyn E. Y.; Mendoza, Jose Christopher E. (Zootaxa, 2013)
The name Cancer lactatus Linnaeus, 1758, has not been treated taxonomically since it was described, with a diagnosis provided by Linnaeus (1758: 627): “C[ancer] brachyurus, thorace laevi utrinque serrato-quadrilobo, manibus ovatis laevibus. M.L.U. Habitat in Indiis.”. The abbreviation, “M.L.U.”, in Linnaeus (1758: 627) refers to the Museum Ludovicae Ulricae (Linnaeus 1764), a study of the collection of Queen Louisa Ulrica which was not published until 1764, but the manuscript of which was ready four years before the publication of the tenth edition of the Systema Naturae (Linnaeus 1758) (see Dance 1967: 13–15). The collection of Queen Ulrica was later presented to the University of Uppsala by King Gustav IV Adolf, where it is now deposited (Dance 1967: 15). This depository is now the Zoology Section, Museum of Evolution, Uppsala University, Uppsala, Sweden (UUZM) (Wallin 2001).